A rare case of retained placenta in a young primigravida with no known risk factors; managed by manual removal of the placenta under general anaesthesia - Sah, Ravi; Gaurav, Amrita; Kumari, Om; Yadav, Kripa; Ravichandran, Nevetha; Kumar, Rajan; Gautam, Saurabh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A retained placenta is suspected when there is failure of expulsion of the placenta even after 30 minutes of delivery of the fetus. Retained placenta is a common cause of PPH and, hence, a significant cause of maternal mortality and morbidity in developing countries. Thus, early intervention is necessary to prevent this post-delivery of the baby. We present a case of retained placenta in a young primigravida with oligohydramnios with fetal horse horseshoe-shaped kidney and a foetal echogenic bowel loop. Her clinical findings and investigations were not significant at the time of admission. She was induced with dinoprostone gel intra-cervically and delivered via vaginal route. There was failure of expulsion of the placenta even after 30 minutes of delivery of the baby. Inj. syntocin 5 units were given via the umbilical cord. In the event of this failure, the patient was shifted inside the OT, and manual removal of the placenta was done under general anaesthesia f/b evacuation retained bits of placental membranes with ovum forceps under USG guidance. Retained placenta can lead to severe PPH and its consequences in the postpartum period. Thus, it requires timely intervention to prevent PPH and reduce maternal mortality and morbidity. Cases of retained placenta can occur even in the absence of any known identified risk factors and should be managed in a tertiary care centre with OT facilities.